Identification and Functional Analysis of EPOR+ Tumor-Associated Macrophages in Human Osteosarcoma Lung Metastasis - Yanxing Li; Ming Li; Rong Wei; Junlong Wu (Journal of Immunology Research)
Background. Tissue-resident macrophages can be educated to tumor-associated macrophages (TAMs) by the tumor microenvironment and many types of macrophages express erythropoietic receptor (EPOR); However, little is known about the expression of EPOR on TAMs and the identity of EPOR+ TAMs in osteosarcoma lung metastasis has thus far remained elusive. Methods. EPOR-eGFPcre mice were used to determine the expression of EPOR on lung tissue-resident macrophages. Flow cytometry, RT-PCR, and Western blot were examined to define the identity of EPOR+ TAMs in 106 osteosarcoma lung metastasis specimens. Moreover, the clinicopathologic factors and prognosis of patients with CD163+EPOR+ macrophages were compared. Results. We found that a subpopulation of mouse lung tissue-resident macrophages express EPOR and EPO enhances the proliferation of EPOR+ macrophages in mouse lung. A subpopulation of CD163+ macrophages expresses EPOR in human osteosarcoma lung metastasis specimens. CD163+EPOR+TAMs increase 2.5 times in human osteosarcoma lung metastasis tissues; CD206, CD163, and PD1, which are known to have a significant role in TAM function had high expression in CD163+EPOR+ TAMs compared with CD163+EPOR- TAMs. Furthermore, CD163+EPOR+ TAMs had higher M2 marker and cytokine expression in osteosarcoma tissues compared with para-osteosarcoma tissues. EPO enhanced the expression of M2 cytokines in primary CD163+EPOR+ TAMs. Importantly, the percentage of CD163+EPOR+ TAMs had a positive linear association with malignant phenotypes as well as poor disease-free survival and overall survival time. Conclusions. We have characterized TAMs expressing EPOR and CD163+EPOR+ macrophages as TAMs in osteosarcoma lung metastasis patients, which are highly associated with tumor aggressiveness.